Peran Influencer Terhadap Niat Pembelian Produk Fashion Gen Z Melalui Perbandingan Sosial, FOMO, dan Materialisme - Putri, Stevani Tri Wahyu; Rahayuningtyas, Tri Esti; Negara, Wana Pramudyawardana Kusuma (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The development of social media has enhanced the role of influencers in shaping consumer behavior, particularly among Gen Z. Influencers act not only as sources of information but also as role models who encourage imitative behavior, social comparison, fear of missing out (FOMO), and materialism, which ultimately influence fashion purchase intention. This study aims to analyze the effect of influencer imitation on fashion purchase intention through social comparison, FOMO, and materialism among Gen Z in East Java. This research employs a quantitative approach using a survey method. Data were collected through an online questionnaire using a Likert scale and involved 248 Gen Z respondents residing in East Java who follow influencers on social media and actively use e-commerce platforms. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach through SmartPLS version 4.0. The results indicate that influencer imitation has a positive and significant effect on social comparison, FOMO, and materialism. Furthermore, social comparison and FOMO are proven to have a positive and significant effect on fashion purchase intention. Materialism also shows a positive and significant effect on purchase intention, although its contribution is relatively smaller than that of FOMO. These findings demonstrate that the influence of influencers on purchase intention is not only direct but also strengthened through psychological and social mechanisms. This study is expected to contribute theoretically to consumer behavior literature and provide practical considerations for fashion industry practitioners and marketers in designing more effective marketing strategies targeting Gen Z.